2019
DOI: 10.1111/nph.15815
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid is a substrate of the ABC transporter encoded by the durable wheat disease resistance gene Lr34

Abstract: Summary The wheat Lr34res allele, coding for an ATP ‐binding cassette transporter, confers durable resistance against multiple fungal pathogens. The Lr34sus allele, differing from Lr34res by two critical nucleotide polymorphisms, is found in susceptible wheat cultivars. Lr34res is functionally transferrable as a transgene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(66 citation statements)
references
References 73 publications
2
50
0
1
Order By: Relevance
“…Furthermore, lots of DEGs were markedly enriched into plant hormone signal transduction pathway. Consistently, it has been reported that auxin [74,75], cytokinins [76,77], ethylene [75,[78][79][80], gibberellin [81], abscisic acid [75,82,83], brassinosteroids [80], salicylic acid [75,78,84], jasmonic acid [75,78,[84][85][86], strigolactones [87] can actively participate in disease response. Among them, salicylic acid signal transduction and jasmonic acid/ethylene signal transduction are considered as the most common plant hormone signal transduction pathways in response to biological or abiotic stress.…”
Section: Discussionsupporting
confidence: 55%
“…Furthermore, lots of DEGs were markedly enriched into plant hormone signal transduction pathway. Consistently, it has been reported that auxin [74,75], cytokinins [76,77], ethylene [75,[78][79][80], gibberellin [81], abscisic acid [75,82,83], brassinosteroids [80], salicylic acid [75,78,84], jasmonic acid [75,78,[84][85][86], strigolactones [87] can actively participate in disease response. Among them, salicylic acid signal transduction and jasmonic acid/ethylene signal transduction are considered as the most common plant hormone signal transduction pathways in response to biological or abiotic stress.…”
Section: Discussionsupporting
confidence: 55%
“…Isolation of APR genes Pm38 and Pm46 identified a single gene encoding an ATP‐binding cassette (ABC) transporter (Krattinger et al , 2009) and a hexose transporter (Moore et al , 2015), respectively, at the multipathogen resistance locus, which confers dual resistance for wheat leaf rust and stripe rust in addition to powdery mildew. These two genes were hypothesized to undergo similar defence activation relating to a coordinated interaction of abscisic acid (ABA) and sugar signalling (Moore et al , 2015; Krattinger et al , 2019). Sugar signals have been postulated to act as priming molecules leading to PTI and ETI (Bolouri Moghaddam and van den Ende, 2012), regulating plant metabolism induced by the pathogen.…”
Section: Resistance Types For Powdery Mildewmentioning
confidence: 99%
“…Despite the fact that incorporating APR into new cultivars can be difficult when compared to ASR, it was found that many wheat cultivars possessing APR showed durable resistance (Mcintosh, 1992;Boyd, 2005;Navabi et al, 2005;Singh et al, 2005;Ren et al, 2012b;Chen, 2013;Randhawa et al, 2018). Some APR genes when used in combinations have been known to possess durable pleiotropic resistance against multiple wheat rusts and powdery mildew, i.e., Lr34/Yr18/Sr57/Pm38 (on chromosome 7DS), Lr46/Yr29/Sr58/Pm39 (on chromosome 1BL), and Lr67/Yr46/Sr55/Pm46 (on chromosome 4DL) (Lagudah, 2011;Risk et al, 2012;Ellis et al, 2014), of which Lr34 has been studied extensively in different crops including rice, barley, maize, and sorghum (Krattinger et al, 2013(Krattinger et al, , 2019. Deployment of seedling (all-stage resistance), adult plant (non-race specific and race-specific) and slow rusting resistance is to create diversity for resistance (Bhardwaj et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%